2016
DOI: 10.1111/eth.12506
|View full text |Cite
|
Sign up to set email alerts
|

Independent Mating Preferences for Male Body Size and Coloration in Female Trinidadian Guppies

Abstract: Although females in numerous species generally prefer males with larger, brighter and more elaborate sexual traits, there is nonetheless considerable intra‐ and interpopulation variation in mating preferences amongst females that requires explanation. Such variation exists in the Trinidadian guppy, Poecilia reticulata, an important model organism for the study of sexual selection and mate choice. While female guppies tend to prefer more ornamented males as mates, particularly those with greater amounts of oran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 96 publications
(209 reference statements)
1
31
0
Order By: Relevance
“…For any given pair of stimulus males (both unmated) in Treatment 3 of the control trials, the male that had previously been in the right end compartment of the dichotomous-choice apparatus (at the onset of tests in Treatments 1 and 2) was denoted the Right male and the male that had been in the left end compartment was denoted the Left male. Statistical results shown were obtained using the Wilcoxon paired signed rank test (n = 20 for both experimental and control trials) when they had only visual cues originating from the males available to them (Treatment 2), presumably because the paired males were similar in phenotypic traits (namely, body length, body weight, body colouration and sexual behaviour) that are known to influence female mate choice in the guppy (Auld et al, 2016;Endler & Houde, 1995;Houde, 1997) and they had not previously observed either male sexually interact with other females, a context which can provide potential public visual information on male functional fertility (Scarponi et al, 2015). As revealed by our control trials, when both paired males were unmated and had fully intact sperm stores and were similar in measured phenotypic traits, females did not exhibit any mating preference for either male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For any given pair of stimulus males (both unmated) in Treatment 3 of the control trials, the male that had previously been in the right end compartment of the dichotomous-choice apparatus (at the onset of tests in Treatments 1 and 2) was denoted the Right male and the male that had been in the left end compartment was denoted the Left male. Statistical results shown were obtained using the Wilcoxon paired signed rank test (n = 20 for both experimental and control trials) when they had only visual cues originating from the males available to them (Treatment 2), presumably because the paired males were similar in phenotypic traits (namely, body length, body weight, body colouration and sexual behaviour) that are known to influence female mate choice in the guppy (Auld et al, 2016;Endler & Houde, 1995;Houde, 1997) and they had not previously observed either male sexually interact with other females, a context which can provide potential public visual information on male functional fertility (Scarponi et al, 2015). As revealed by our control trials, when both paired males were unmated and had fully intact sperm stores and were similar in measured phenotypic traits, females did not exhibit any mating preference for either male.…”
Section: Discussionmentioning
confidence: 99%
“…Using Image J software (http://imagej.nih.gov/ij/), we measured the standard body length of each fish and quantified the body colour ornamentation of each stimulus male from their digital photograph as follows. We separately quantified the areas of black (melanin) and orange-yellow pigmentation (hereafter orange colour) on the left side of each male's body, excluding the fins.Black and orange colouration in males are sexually selected through female mate choice in the Trinidadian guppy(Endler & Houde, 1995;Houde, 1997), and females from our study population prefer males with more orange and black colouration on their body as mates(Auld et al, 2016). To control for inter-individual differences in body size, we then calculated the relative area of total body colour ([Black area + Orange area]/Total body area) for each male as their individual colour ornamentation score.…”
mentioning
confidence: 99%
“…In the first experiment, the stimulus females differed in body length (i.e., small vs. large females presented) and the average difference in their length was similar across treatments. I manipulated the relative sexual attractiveness and competitiveness of observer and model males by choosing males of same or different body length and body coloration, two sexually-selected traits in the guppy (Houde 1997;Auld et al 2016), in each of four treatments. I predicted that, focal observer males should be more likely to reverse their initial mate-choice (i.e., mate-choice copy) decision when social information is available, relative to when social information is not available.…”
Section: Thesis Objective Predictions and Organizationmentioning
confidence: 99%
“…Makowicz et al 2010b;Chapter 6). Sexual rivals also vary both in their ability to attract and mate with females and the ability of their sperm to fertilize eggs (Brooks and Endler 2001;Brooks 2002;Pilastro et al 2002;Locatello et al 2006;Auld et al 2016;Chapter 3).…”
Section: Introductionmentioning
confidence: 99%
“…In my study population in Trinidad, large and(or) more colour ornamented males are expected to be more sexually attractive and competitive than smaller and(or) drabber males because females prefer larger and more ornamented males as mates (Magellan et al 2005;Auld et al 2016; Chapter 3; but see Schwartz and Hendry 2007) and more ornamented males (possessing more orange and black colour on their body) produce faster and more viable sperm than drabber males (Locatello et al 2006), suggesting that more ornamented males have a competitive advantage in sperm competition over less ornamented ones. Irrespective of body ornamentation, large male guppies might also outcompete smaller rival males for access to females through sneak copulation, because burst swimming and body rotational velocities are positively correlated with body size in this species (Ghalambor et al 2004).…”
Section: Introductionmentioning
confidence: 99%